When Environmental Transparency Meets Profitability: The Impact of Carbon Emission Disclosure and Green Investment on Firm Value in Mining Companies - Jihan Putri Syabila; Veronika Santi Paramita (Indonesian Scientific Publication, 2026)
This study examines the valuation of publicly listed mining companies in a specific sub-sector on the Indonesia Stock Exchange during 2020–2024, a period marked by increasing global attention to climate change and ESG transparency. The mining sector faces growing scrutiny due to its carbon emissions and role in the transition toward a sustainable economy. This research analyses the impact of carbon emission disclosure and green investment on firm value, with profitability as a moderating variable. A quantitative descriptive-causal approach was employed using secondary panel data from financial and sustainability reports. Eight mining sub-sector companies were selected through purposive sampling, and the data were analysed using panel data regression and moderated regression analysis (MRA). The results show that green investment does not significantly affect firm value. In contrast, carbon emission disclosure has a negative effect on firm value, indicating that increased transparency may heighten investor concerns regarding environmental risks and compliance costs. However, profitability significantly moderates this relationship by reducing the negative impact of carbon emission disclosure and strengthening the effect of sustainability practices on firm value. These findings imply that transparent carbon emission reporting should be accompanied by strong profitability to enhance firm value. This study extends prior sustainability and firm value research by providing empirical evidence on the moderating role of profitability in Indonesia’s mining sub-sector.